Dynamics of the welfare of dairy cattle affected by podopathies as support for veterinary expertise - Amaral, Jackson Barros do; Ambrósio, Luís Alberto (Pubvet, 2022)
Due to the necessity for treatment and prevention of production diseases, such as podopathies, dairy cattle welfare expertise is an innovative and relevant demand in legal and forensic investigations. Veterinary technicians can establish the negligence, malpractice, and imprudence in animal care, and would support judicial decision, in cases of cattle mistreatment, cruelty, and abuse. A dynamic approach is required to understand the podopathies complexity due to non-linear interactions between multifactors and cattle welfare. System Dynamics methodology was used to build a conceptual model of podopathies problems and constructs cause-and-effect relationships based on knowledge and experience of the researchers and literature. The model contains six diagrams with reinforcing and balancing cycles and the respective state variables reference patterns. The dynamic hypotheses highlighted the role of veterinary expertise in assessing the reinforcing the podopathies and welfare interaction that drives the system into a virtuous or vicious circle. It was detailed how podopathies cause pain and suffering, further reinforcing the loss of welfare. The veterinarian's action, motivated by ethical, legal, or social pressure, to promote prevention and treatment, creates balance feedbacks that might elevate welfare to the desired level. The prevention cycles have delayed actions effects on podopathies, resulting in the continuity of pain and suffering, for some time. A counterintuitive synergy emerged between the use of financial resources for production and investments to ensure welfare. As a result, promoting health balancing cycles, reducing podopathies and improving animal welfare positively influence economic. Expertise through negative feedback based on technical, legal, ethical, and human values controls the podopathies incidence influencing actions to improve the welfare. It was concluded that the conceptual model serves as a framework to aid computational modeling and contributes to better understanding of the podopathies complexity in legal and forensic matters. Human actions influence podopathies dynamics, which compromise animal welfare and may lead to evidence of abuse in dairy cattle.
Keywords: Foot disorders; bovine; forensic veterinary medicine; conceptual model; feedback